ANALYSIS OF THE INFLUENCE OF MARKETING PUBLIC RELATIONS AND COMPANY IMAGE ON VISIT DECISIONS TO MEKASARARI FRUIT GARDEN - Renaldo Aswansyah Putera; Aminah Swarnawati (Jurnal Info Sains : Informatika dan Sains, 2022)
Marketing public relations is a major factor in the tourism industry in Indonesia for tourist attractions experiencing issues and crises to try to bounce back from adversity. This quantitative study aims to obtain information on marketing public relations and corporate image at Mekarsari Fruit Park and to determine its influence on the decision to visit the community after the Covid-19 pandemic. This study involved 1,376,734 people selected by random sampling as many as 94 respondents from a questionnaire that had been distributed using a survey, where the data obtained was analyzed using the SPSS statistical application. The results of this study are that marketing public relations and corporate image influence the decision to visit the community at Mekarsari Fruit Park. Following up on the findings of this research, marketing public relations needs to be carried out in the tourism industry where entrepreneurs and the government collaborate to develop sustainable programs in the hope that the tourism creative economy will grow again